Psikologi Pendidikan Islam berbasis Hadis: Membangun Kerangka Ilmiah untuk Pengembangan Karakter, Emosi, dan Motivasi Belajar Siswa - Darlina Nuralisyarifah Marzuki; Fadhilah Fadhilah; Yoprisya Yoprisya; Inong Satriadi (Prodi Pendidikan Keagamaan Islam, 2026)
Integrating Islamic values into educational psychology is essential for fostering students’ character, emotional regulation, and learning motivation. This study aims to identify psychological principles in the Hadith of Prophet Muhammad relevant to education, analyze their contribution to student development, and develop an integrative conceptual framework for contemporary Islamic education. A qualitative conceptual-analytical approach was employed, combining thematic analysis of selected Hadith and relevant scholarly literature. The findings reveal that Hadith emphasize ethical modeling, emotional management, and intention-based motivation, which together form a coherent and holistic framework for student development. The study concludes that a Hadith-based educational psychology framework provides practical guidance for educators in designing learning strategies that strengthen character, stabilize emotions, and enhance intrinsic motivation, offering a valuable theoretical and practical contribution to the advancement of contemporary Islamic education.